BUILDING AWERENESS ON TOURISM BY THE LOCAL COMMUNITY AND TOURIST AT TANJUNG BAYANG BEACH, INDONESIA - Mutiara Arwini (Politeknik Pariwisata Makassar, 2025)
This study aims to analyze the level off awereness of local communities and tourist and identify the role of local communities as stakeholders. Tourism awareness is a crucial factor in maintaining destination sustainability. This research focuses on the level of awareness among local communities and tourists at Tanjung Bayang Beach, Makassar. Despite its attractive natural and cultural potential, it still faces challenges related to cleanliness, community participation, and limited supporting facilities. The research objective is to analyze the current state of tourism awareness and provide recommendations for sustainability-based management strategies. The research method used a qualitative approach with case studies, through direct observation, interviews, and on-site documentation. Data were analyzed using a SWOT analysis to identify strengths, weaknesses, opportunities, and threats influencing the development of tourism awareness. The results indicate that the main strengths lie in the potential of natural attractions, local cultural support, and the community's spirit of mutual cooperation. However, weaknesses remain, such as limited understanding of tourism potential among some residents, tourists' lack of environmental awareness, and a lack of basic facilities. Opportunities, however, arise through the use of social media, government programs, and increased tourist interest. Threats include environmental damage, conflicts of interest, and inadequate management regulations.The conclusion of this study confirms that increasing tourism awareness must be a collaborative effort between the community, tourists, managers, and the government. Recommendations include improving tourism awareness education, providing supporting facilities, and strengthening the role of local communities as key stakeholders. Thus, tourism at Tanjung Bayang Beach has the potential to develop sustainably without sacrificing environmental sustainability or local cultural values.